The effect of a training program using concentric/overload eccentric exercises on maximum strength, achievement record and some dynamic variables of snatch lift - Essam AbouGamil (Turkish Journal of Kinesiology, 2017)
This research aimed to find the effect of using Concentric/Overload Eccentric Exercises (Co/OvEc-Exs) to improve maximum strength (MS) level in the weightlifting training program on both of (M.S.) level, achievement record of snatch lift (ARSF). In addition, dynamic variables of Time (Ti), acceleration (Ac), work (Wo), and power (Po), through the two phases of (drop & turnover under the barbell) and (catch & stable standing) of snatch lift. The researcher used the experimental method by the design of per – post measurements of two equal groups, one of them was the control group (Cl group) and the other was the experimental group (El group), each group consisted of 5 weightlifters. Equality between the two groups was conducted in variables of age – height – weight – training age, MS variables of the performance level on tests of Clean – Jerk – Power Squat – Front Squat – Snatch Pull, ARSF, and those dynamic variables. To achieve the research purpose, a training program was applied for 10 weeks on the two groups.  It included 30 training units – 3 units weekly, MS exercises for Cl group were performed in the traditional mode – concentric/eccentric exercises Co/Ec-Exs, in which the concentric and eccentric portions of the exercise cycle was performed with a constant weight which was equivalent 80-90٪ of the weightlifter's maximum load. While the same exercises were performed for the (El group) in the intended non-traditional mode of the research – (Co/Ov Ec-Exs) in which the concentric portion was performed with 80 - 90٪ load but the eccentric portion was performed with an equivalent load to 110 - 120٪ of the weightlifter's maximum load and this portion must be performed in a period of 3-5 sec.  This was with taking into account that the concentric portion of all exercises for the two groups must be performed explosively. The research results indicated that there were statistically significant differences between the post-measurements of the two groups in all of the experimental variables. Based on these results, it was concluded that the Co/OvEc-Exs are more efficient than Co/Ec-Exs in improving the level of MS which leads to improve the dynamic variables of performing snatch lift, and all of these in turn leads to improve ARSF.